2021
DOI: 10.1080/16549716.2021.1898130
|View full text |Cite
|
Sign up to set email alerts
|

Availability and advertising of sugar sweetened beverages in South African public primary schools following a voluntary pledge by a major beverage company: a mixed methods study

Abstract: Background: Towards the end of the 2017 school year, a prominent beverage company in South Africa pledged to remove their sugar-sweetened beverages (SSBs) and advertisements from primary schools in order to contribute to the realization of a healthy school environment. Objectives: To assess the availability and advertising of the company's beverages in public primary schools in Gauteng province following their voluntary pledge to remove the products, and to explore perceptions of school staff regarding SSB ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 23 publications
1
25
0
Order By: Relevance
“…As with other legislative measures like taxation, marketing regulations have been contested in favor of self-regulation by industry, which studies have shown to be ineffective [ 80 , 81 ]. In South Africa for instance, SSB advertisements were still present in most primary schools despite the voluntary pledge made by industry not to advertise their products in schools [ 82 ]. Zambia could draw an implementation lesson from the restriction of marketing of breast milk substitutes, which has been in place for over a decade [ 83 ], to strengthen the design of marketing restriction of unhealthy food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…As with other legislative measures like taxation, marketing regulations have been contested in favor of self-regulation by industry, which studies have shown to be ineffective [ 80 , 81 ]. In South Africa for instance, SSB advertisements were still present in most primary schools despite the voluntary pledge made by industry not to advertise their products in schools [ 82 ]. Zambia could draw an implementation lesson from the restriction of marketing of breast milk substitutes, which has been in place for over a decade [ 83 ], to strengthen the design of marketing restriction of unhealthy food and beverages.…”
Section: Discussionmentioning
confidence: 99%
“…The school environment has been extensively researched as a place where adolescents are present for a large part of their day and is considered an important determinant for food choices, contributing to the consumption of unhealthy foods (18,(27)(28)(29)(30)(31)(32). International studies have found that SSB availability in the school food environment is associated with the purchase and consumption of these beverages by children and adolescents (27,(33)(34)(35)(36).…”
Section: Introductionmentioning
confidence: 99%
“…These factors influence people’s food choices and nutritional status. There is substantial evidence suggesting that the community-level physical food environment contributes to the high levels of obesity and diet-related disease [ 60 , 61 , 62 , 63 , 64 , 65 ]. Few articles published in LMICs on the topic include studies where it is shown that most of the foods sold in the community convenience stores and by street vendors do not foster good health [ 57 , 59 ].…”
Section: Diet-related Public Health Approaches Aimed For This Special...mentioning
confidence: 99%
“…However, we must be cognizant that the demand by consumers is a key determinant of the food offered by these informal food outlets [ 58 , 66 ]. This is also the case in terms of the type of food sold in schools, as evidence [ 67 , 68 ] has shown that the reason why this food is mostly unhealthy [ 69 ] is because children demand unhealthy food [ 70 ], and their preference for this food is fueled by food marketing [ 61 ]. This has a strong policy implication; hence, policy reforms are required to increase access to affordable healthy food options in communities and schools, so as to curb the indiscriminate sale and marketing of unhealthy food.…”
Section: Diet-related Public Health Approaches Aimed For This Special...mentioning
confidence: 99%